Molecular cloning of the cell surface antigen identified by the osteoprogenitor-specific monoclonal antibody, HOP-26. - Zannettino, A; Harrison, K; Joyner, C; Triffitt, J; Simmons, P (2003)
Bone is a highly organized structure comprising a calcified connective tissue matrix formed by mature osteoblasts, which develop from the proliferation and differentiation of osteoprogenitor cells. The osteogenic cell lineage is thought to arise from a population of uncommitted multipotential stromal precursor cells (SPC) which reside close to all bone surfaces, in the bone marrow spaces and the surrounding connective tissue. These SPC also give rise to related cell lineages which form cartilage, smooth muscle, fat, and fibrous tissue. Due to the lack of well defined cell surface markers, little is known of the precise developmentally regulated changes in phenotype which occur during the differentiation and maturation of human osteoprogenitor cells into functional osteoblasts and ultimately, terminally differentiated osteocytes. In order to identify antibody reagents with greater specificity for osteoprogenitors we generated a series of antibodies following immunization with freshly isolated human bone marrow stromal fibroblasts. One such antibody, HOP-26, reacts with a cell surface antigen expressed by SPC and developing bone cells. We now demonstrate that this mAb identifies a member of the tetraspan family of cell surface glycoproteins, namely CD63. Western blot analysis of human bone marrow stromal cells (HBMSC) has revealed that like a well defined CD63 mAb 12F12, HOP-26 interacts with a heavily glycosylated cell surface protein with an apparent molecular weight of 50-60 kD.